2020
DOI: 10.1590/0034-7167-2019-0234
|View full text |Cite
|
Sign up to set email alerts
|

Transition of blind women to motherhood from the perspective of Transitions Theory

Abstract: Objective: to analyze the transition of blind women to motherhood from the perspective of Transitions Theory. Method: a qualitative, descriptive study, which had as participants 11 blind women. An open interview was conducted using the narrative method. Analysis occurred in the light of Transitions Theory, with approval from the Research Ethics Committee with Human Beings. Results: the age group was 32 to 63 years, mostly Catholic, with social security benefits. Transition to motherhood mainly evidenced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
6
0
5
Order By: Relevance
“…It was important for them to reflect on child-rearing in the community and build new relationships and connections to get the sense that child-rearing was not only an individual effort, but was also positioned in the community and society through child-rearing support. Several previous studies on transition to motherhood have referred to partner and family support and the changed relationships with them [ 9 , 11 , 12 , 13 ], with similar results to this study, which showed that building new relationships and connections was key. Conversely, a new finding of reflecting on child-rearing in the community was clarified as a transition condition, not only the relationships with partners and families.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It was important for them to reflect on child-rearing in the community and build new relationships and connections to get the sense that child-rearing was not only an individual effort, but was also positioned in the community and society through child-rearing support. Several previous studies on transition to motherhood have referred to partner and family support and the changed relationships with them [ 9 , 11 , 12 , 13 ], with similar results to this study, which showed that building new relationships and connections was key. Conversely, a new finding of reflecting on child-rearing in the community was clarified as a transition condition, not only the relationships with partners and families.…”
Section: Discussionsupporting
confidence: 86%
“…Since most of the existing research on the transition to motherhood has studied white, married, and middle-class individuals, it is necessary to expand it to a wider range of socioeconomic classes and to more culturally diverse participants as they transition into motherhood [ 9 ]. Recently, there have been studies targeting adolescent mothers [ 10 ], blind women [ 11 ], women in wheelchairs [ 12 ], and women with infants with special care needs [ 13 ]. A review has shown that the transition to motherhood includes two inherent processes: (1) engagement and (2) growth and transformation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with earlier reports on audition in the blind that suggest that ecological relevance is the key factor for cross‐modal plasticity (Gougoux et al., 2004). In rodents literature, behavioral adaptations were also reported in early blind women who displayed prolonged duration of breastfeeding beyond the first year postpartum, accompanied by increased physical contact/proximity and more frequent vocalizations toward their newborn (Chiesa et al., 2015; Ganea et al., 2018; Santos & Ribeiro, 2020; Thoueille et al., 2006). In addition, enhanced attentional processes to respond to auditory and haptic stimuli have been evidenced in blind humans, which may contribute to heightening nonvisual sensory skills (Collignon & De Volder, 2009; Collignon et al., 2006; Hugdahl et al., 2004; Liotti et al., 1998; Pigeon et al., 2015; Topalidis et al., 2020).…”
Section: Discussionmentioning
confidence: 97%
“…For women with disabilities, prejudice and discrimination related to the exercise of motherhood emerge in family and close relationsh ips 18,[32][33][34][35][37][38][39]41,42,44,[50][51][52][53]56,57,[60][61][62][64][65][66][67][68]70,76,77,79 .…”
Section: Infantilization Dehumanization and Discredit In Motherhood E...mentioning
confidence: 99%
“…Obstetric violence of an enabling nature is not an individual phenomenon but a long-term structure based on models of the body, norms of its presentation, and function. It is expressed in the carelessness that words, gestures, and glances reveal when ignoring or not welcoming the presence of women with disabilities in the care spaces for pregnant women 33,[35][36][37][38][39]42,44,[47][48][49][50][53][54][55]58,61,62,[64][65][66][67]69,75,77,79,[81][82][83] , including recommending abortion or sterilization when these women express interest or want information about their sexual and reproductive health 35,45,58 . Obstetric ableism is reflected in the environmental barriers found in health servi ces 36,53,62,63,66,74,76,[78][79][80][81]83 , in the denial of sexuality and, alongside this, the right to reproductive decisions tailored to the needs demanded by the diversity of expressions of disability…”
Section: Obstetric Ableism: Expression Of Obstetric Violencementioning
confidence: 99%